2021
DOI: 10.1016/j.radonc.2020.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Non-operative management for oral cavity carcinoma: Definitive radiation therapy as a potential alternative treatment approach

Abstract: Highlights: Definitive RT/CRT for OSCC achieved acceptable rate of locoregional control. Definitive RT is a reasonable alternative treatment strategy if surgery is not possible. cN2-3 is associated with poor distant control, DFS, and OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 40 publications
6
20
3
Order By: Relevance
“…In addition, the results suggest a potential effect of dose escalation on local control. The acute radiation toxicity in the cohort was comparable to the results reported in other published studies [ 7 , 17 , 18 , 22 ] using different radiotherapy techniques and doses. No acute CTCAE grade 4 toxicity manifested.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In addition, the results suggest a potential effect of dose escalation on local control. The acute radiation toxicity in the cohort was comparable to the results reported in other published studies [ 7 , 17 , 18 , 22 ] using different radiotherapy techniques and doses. No acute CTCAE grade 4 toxicity manifested.…”
Section: Discussionsupporting
confidence: 86%
“…This is comparable to the results of studies with different dose-escalation techniques [ 12 , 26 , 27 ]. Hosni et al [ 7 ] published the results for 108 patients with T1–T4 stage oral cavity tumors treated with definitive radiochemotherapy; after a median follow-up of 52 months, osteonecrosis developed in 6.6% of the patients. Foster et al [ 28 ] reported the incidence of osteonecrosis and long-term feeding tube dependence in 20.7% and 10% of patients after definitive radiochemotherapy in 140 patients with oral cavity cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the presented cohort offers certain peculiarities that should be respected concerning treatment planning. Although primary radiotherapy is a valuable option for radiation-naive patients suffering from head and neck cancer that offers good local and regional control rates, there are advantages of a primary surgical approach that should be considered [ 13 ]. These include the possibility to further improve the outcome if complete tumor resection is achieved, to guide adjuvant therapy by possibly detecting occult lymph node metastases, and to restore areas where extensive tumor growth may lead to defect healing if primary radiotherapy is applied.…”
Section: Discussionmentioning
confidence: 99%